Moving Beyond Religious Clichés: A Review - Hubina, Milos (Numen, 2022)
The article reviews the most recent systematic effort to correct some of the widespread misconceptions about religion: Brad Stoddard and Craig Martin’s edited volume Stereotyping Religion: Critiquing Clichés (2017) and Tenzan Eaghll’s article “Religious Clichés” (2015). It argues that the joint goal becomes problematic due to some empirical and logical distortions, which mainly result from the emphasis on the relativist message offsetting the impartial assessment of facts and their implications. It argues for integrating the biological and cultural explanations of religion and offers some proposals toward identifying the contemporary clichés that impede progress in our understanding of the phenomenon.